Digital transformation and organizational performance in port logistics: The mediating role of supply chain performance in an emerging economy - Haryono, Haryono; Kusmaningtyas, Amiartuti; Pristiana, Ulfi (Edelweiss Applied Science and Technology, 2026)
The purpose of this study is to investigate the effect of digital transformation on organizational performance through the mediating effects of supply chain performance. Specifically, the benefits of IoT adoption, the challenges of IoT adoption, and the capabilities of information systems are considered as factors driving digital transformation. Based on the Resource-Based View (RBV) theory and Supply Chain Network Theory (SCNT), an elaborate model was constructed and tested. A quantitative explanatory approach was used in this research, and data collection involved survey questionnaires administered to 120 managers, IT officers, and logistics practitioners working for multipurpose ports in East Java, Indonesia. PLS-SEM technique was adopted for the statistical analysis of data collected. The study’s findings show that the benefits of IoT adoption and capabilities of information systems exert significant and positive influence on supply chain performance and organizational performance. The mediator effect of supply chain performance was confirmed in both relationships. Challenges of IoT adoption do not significantly impact neither supply chain performance nor organizational performance. Digital transformation improves organizational performance via improvement of supply chain performance. It is recommended that port logistics firms invest more in IoT adoption and enhance their supply chains.